Position paper on requirements for toxicological studies in the specific case of radiopharmaceuticals - J. Koziorowski; M. Behe; C. Decristoforo; J. Ballinger; P. Elsinga; V. Ferrari; P. Kolenc Peitl; S. Todde; T. L. Mindt (SpringerOpen, 2016)
Abstract This is a position paper of the Radiopharmacy Committee of the EANM (European Association of Nuclear Medicine) addressing toxicology studies for application of new diagnostic and therapeutic radiopharmaceuticals (RP) that are not approved (i.e., not having a marketing authorization or a monograph in the European Pharmacopoeia), excluding endogenous and ubiquitous substances in humans. This paper discusses the requirements for clinical trials with radiopharmaceuticals for clinical research applications, not necessarily intended to aim at a marketing authorization. If marketing authorization is intended, scientific advice of the competent authorities is mandatory and cannot be replaced by this position paper. The position paper reflects the view of the Radiopharmacy Committee of the EANM and can be used as a basis for discussions with the responsible authorities.